Challenges and Threats of the Global Information Society - E. Zinovieva (Международная аналитика, 2015)
The article investigates the challenges and risks to international security arising from the development of the global information society. The basic trends of the global information society development are analyzed, as well as theoretical approaches to the theory of information society. The author also assesses the impact of the global information society development on the world politics. The paper examines the main challenges, risks and threats arising from the development of the global information society, as well as the prospects for international cooperation in the field of international information security.